2021
DOI: 10.3390/educsci11020054
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of EAP Teachers’ Views and Experiences of E-Learning Technology

Abstract: The near universal use of electronic learning (e-learning) in higher education (HE) today requires that students and teachers are equipped with the requisite digital literacy skills. The small-scale pilot study we report on here explored the views and experiences of EAP (English for Academic Purposes) teachers regarding their development of digital literacy skills, their application of e-learning technology in their teaching, and their perceptions of its value as a learning tool—areas on which there has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
2
17
0
1
Order By: Relevance
“…However, most of them (85%) appeared to favor "self-taught" for every tool listed (9/9) in the survey, which also can be found in the qualitative data. This finding aligns with Dhillon and Murray's (2021) study which reported that the majority of the EAP teachers learned e-learning tools themselves. In their study, it was found that the teachers' previous qualifications had equipped them to self-improve their IT skills.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, most of them (85%) appeared to favor "self-taught" for every tool listed (9/9) in the survey, which also can be found in the qualitative data. This finding aligns with Dhillon and Murray's (2021) study which reported that the majority of the EAP teachers learned e-learning tools themselves. In their study, it was found that the teachers' previous qualifications had equipped them to self-improve their IT skills.…”
Section: Discussionsupporting
confidence: 92%
“…Kahoot and Quizzlet were perceived as relatively useful tools by the participants as they could be used to consolidate students' learning. This echoes the finding of Dhillon & Murray (2021) who reported that almost half of EAP teachers in their study used quizzes as quick activities to consolidate students learning. The two lowest-ranking tools in the survey are referencing software and note-taking applications with a score of 39% and 34% respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, some problems with the technical infrastructure were sometimes detected in line with previous evidence [22,27], thus requiring a more structured approach and the need to involve the institution in the unavoidably cross-disciplinary child protec-tion training process. Technical aspects should be considered in light of the opportunity of enhanced communication and collaboration between trainees meeting in a digital environment.…”
Section: Strengths and Weaknesses Of The Erica Digital Trainingmentioning
confidence: 76%
“…Istnieje założenie, że ze względu na powszechność technologii e-learningowych w edukacji większość studentów będzie kompetentna w ich używaniu, w szczególności w zakresie prowadzenia badań internetowych, angażowania się w fora internetowe, komunikowania się za pomocą poczty elektronicznej oraz wypełniania i przesyłania zadań drogą elektroniczną przy użyciu platform instytucjonalnych (Dhillon, Murray, 2021). Od nauczycieli natomiast, oprócz korzystania z systemów elektronicznych do prowadzenia dokumentacji, przesyłania materiałów do wirtualnych środowisk nauczania, komunikowania się ze studentami i dostępu do Intranetu, oczekuje się również wykazania się znajomością i kompetencjami w korzystaniu z różnorodnych elektronicznych narzędzi nauczania i uczenia się (Dhillon, Murray, 2021 Podsumowując, należy stwierdzić, iż kierunki prowadzonych dotychczas nielicznych badań dotyczących akceptacji rozwiązań e-learningowych przez nauczycieli obejmują głównie badanie użyteczności systemów i intencji ich użytkowników. W tym kontekście ważne jest ustalenie, jakie czynniki wpływają na akceptację e-learningu.…”
Section: Postrzeganie E-learningu Przez Nauczycieli Na Przykładzie Po...unclassified